A study of urinary tract infections in renal transplant patients - Walele, Abdul Aziz (Department of Medicine, 2023)
Background: Sepsis remains a serious complication in renal transplant recipients. Urinary tract infections (UTI's) are the most common bacterial infection occurring in these patients. The aim of the study was to document the clinical experience of UTI in renal transplant patients. Methods: A descriptive study of UTI occurring in consecutive renal transplant patients attending the transplant clinic, Tygerberg Hospital between 1st January and 31st July 1995 was undertaken. A UTI was defined as a positive organism culture of > 100 000 cfu/ml on a single urine sample. Data were assessed to determine patient demographics, clinical presentation, risk factors and outcome. The infecting organisms and their antibiotic sensitivity spectrum were determined. Results: Of 166 patients, 76 female and 90 male, urinary tract infections were diagnosed in 43 patients. The incidence of UTI was 26% during the study. In the subgroup of patients who received their renal allograft during the study period the cumulative incidence of UTI was 40% at one month, 53% at three months and 55% at six months post-transplantation. Asymptomatic bacteriuria was present in the majority of patients. Symptoms occurred in 18% predominantly in the early post-transplant (<6 months) period. The risk factors for bacteriuria were female sex, peri-operative urinary catheterization, graft rejection episodes and the early post-transplant period. A strongly suggestive risk factor was a high steroid dose effect. Gram-negative organisms were the predominant urinary organisms cultured. E. Coli was the single most common causative organism in both the early and late (>6 months) post-transplant period. Gram-negative organisms were more than 80% sensitive to only gentamicin or ofloxacin. Gram-positive organisms, sensitive to penicillin or cloxacillin, accounted for 22% of infections predominantly in the late post-transplant period. Urinary tract infections complicated by systemic sepsis were associated with a poor outcome. Conclusions: A high incidence of UTI complicates renal transplantation especially during the early post-transplant period. The risk factors observed are relevant to the local experience. An important observation was the antibiotic sensitivity spectrum of the infecting urinary organisms. This may have bearing on management in the renal transplant patient.